(Genesis and Evolution of Relation State – Church in Byzantine Empire - Doroszkiewicz, Warsonofiusz (Poznańskie Studia Slawistyczne, 2016)
Practicaly until today there haven’t appeared objectiv scientific works concerning begining and evolution of the byzantine monarchy. Christian Church after 300 years of awful persecutions came out of the underground and had to find itself in the new reality, had to decide whether reconcile and cooperate with the society, or isolate from the fallen world, as had done sects, and save chosen. Church chose the first option and took responsibility for the salvation of the world. In reality the emperor, the recent persecutor of the Church, must have persuaded christians, that he himself was not only their friend but good-doer also. Therefore in the 4th century beside the Church of the eschatological character appeared a new power of a temporary character. History of the Eastern Roman Empire is also the history of the relationship between Church and the empire focused on the earthly dimension of its mission. The very symbol of this relationship was famous byzantine eagle as a representation of one body and two different ideological trends. However those relations had not always been ideal, more or less those two bodies existed through the period of 1100 years on the principle of symphonia-agreement. After the fall of the Eastern Roman Empire, Church by the will of God survived in order to continue its mission of salvation of the fallen world.